1998
DOI: 10.1016/s0006-3495(98)77972-x
|View full text |Cite
|
Sign up to set email alerts
|

Trimethylamine-N-Oxide Counteracts Urea Effects on Rabbit Muscle Lactate Dehydrogenase Function: A Test of the Counteraction Hypothesis

Abstract: Trimethylamine-N-oxide (TMAO) in the cells of sharks and rays is believed to counteract the deleterious effects of the high intracellular concentrations of urea in these animals. It has been hypothesized that TMAO has the generic ability to counteract the effects of urea on protein structure and function, regardless of whether that protein actually evolved in the presence of these two solutes. Rabbit muscle lactate dehydrogenase (LDH) did not evolve in the presence of either solute, and it is used here to test… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

10
87
0

Year Published

2001
2001
2014
2014

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 138 publications
(97 citation statements)
references
References 50 publications
10
87
0
Order By: Relevance
“…Nevertheless, the calculated and experimental glycine backbone transfer free energies demonstrate reasonable agreement and account for the features of the protein folding ability of TMAO. 15,47,48 We obtained DG tr from the simulated solvation free energy differences between 2M osmolytes and pure water. These calculated transfer free energies of the peptide backbone demonstrated additivity of each incremental unit of the peptide backbone corresponding to a nearly constant change in the free energy for these short oligomers.…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, the calculated and experimental glycine backbone transfer free energies demonstrate reasonable agreement and account for the features of the protein folding ability of TMAO. 15,47,48 We obtained DG tr from the simulated solvation free energy differences between 2M osmolytes and pure water. These calculated transfer free energies of the peptide backbone demonstrated additivity of each incremental unit of the peptide backbone corresponding to a nearly constant change in the free energy for these short oligomers.…”
Section: Discussionmentioning
confidence: 99%
“…Numerous studies have demonstrated that protecting osmolytes, such as trimethylamine N-oxide (TMAO), can force thermodynamically unstable proteins to fold 2 and stabilize folded proteins to withstand harsh conditions such as high temperature and denaturant concentrations. This favorable folding property of TMAO operates in an additive and independent manner with urea, [3][4][5] allowing counteraction of urea's destabilizing effects on protein stability in urea-rich cells. 6 Indeed, urea and TMAO are often found in a 2:1 molar ratio in marine cartilaginous fish, which in vitro has been shown to result in minimally changed stability.…”
Section: Introductionmentioning
confidence: 99%
“…TMAO can restore enzyme function that has been lost because of the presence of urea (6,(10)(11)(12) by restoring the protein to its native structure (13)(14)(15). The mechanism of action of these protective osmolytes is not understood fully; both direct (16)(17)(18)(19) and indirect (13,(19)(20)(21) interactions have been proposed, and the mechanism may be molecule-specific (14).…”
mentioning
confidence: 99%